2017
DOI: 10.1111/cbdd.13076
|View full text |Cite
|
Sign up to set email alerts
|

Screening of curcumin‐derived isoxazole, pyrazoles, and pyrimidines for their anti‐inflammatory, antinociceptive, and cyclooxygenase‐2 inhibition

Abstract: Curcumin has shown pharmacological properties against different phenotypes of various disease models. Different synthetic routes have been employed to develop its numerous derivatives for diverse and improved therapeutic roles. In this study, we have synthesized curcumin derivatives containing isoxazole, pyrazoles, and pyrimidines and then the synthesized molecules were evaluated for their anti-inflammatory and antinociceptive activities in experimental animal models. Acute toxicity of synthesized molecules wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 28 publications
1
52
0
Order By: Relevance
“…[47] A series of pyrazole, pyridopyrazoltriazine, pyrazolotriazine, isoxazole and pyridine-containing products were prepared as a new class of antioxidant agents starting with curcumin and appropriate chemical reagents. [69] 3. Also, pyrazole and isoxazole derivatives were obtained upon treatment of curcumin with hydrazines or hydroxylamine hydrochloride.…”
Section: Curcumin Pyrazole and Isoxazole Analogs As Antioxidant And Amentioning
confidence: 99%
See 1 more Smart Citation
“…[47] A series of pyrazole, pyridopyrazoltriazine, pyrazolotriazine, isoxazole and pyridine-containing products were prepared as a new class of antioxidant agents starting with curcumin and appropriate chemical reagents. [69] 3. Also, pyrazole and isoxazole derivatives were obtained upon treatment of curcumin with hydrazines or hydroxylamine hydrochloride.…”
Section: Curcumin Pyrazole and Isoxazole Analogs As Antioxidant And Amentioning
confidence: 99%
“…[49] Curcumin derived isoxazoles, pyrazoles and pyrimidines were screened for anti-inflammatory and antinociceptive activities. [69]…”
Section: Curcumin Pyrazole and Isoxazole Analogs As Antioxidant And Amentioning
confidence: 99%
“…The observations are similar to the reported results in previous works, in which pyrazole-based analogues showed better cytotoxicity profiles due to their improved solubility and stability. [6,15,16,[18][19][20] Labbozzetta et al reported that curcuminoids sensitize the human hepatic cancer cells to apoptotic effects while pyrazole curcuminoids lacked the interaction with cell -SH groups and glutathione. [13] In other words, the detoxification mechanism is not required for an increased anticancer potency of pyrazole candidates, in which, the pyrazole fragments prevent a Michael addition with thiol nucleophile.…”
Section: In Vitro Cytotoxicity Against Hepg2mentioning
confidence: 99%
“…Experimental and computational studies on curcumin structure demonstrated that the aromatic ring/substituents on it and β-diketone moieties are crucial for biological responses and kinetic stability. [1][2][3][4][5][6][7][8][9][10][11][12] Several synthetic curcumin analogues have been developed through chemical modifications on its pharmacophores such as pyrazole, [6,[13][14][15][16][17][18][19][20] 1,4-thiazepane, [7] monocarbonyl, [8] aza-aromatic, [9] N-alkyl β-enaminone curcuminoids. [10][11][12] to circumvent the limitations of curcumin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation